2009
DOI: 10.1111/j.1751-8369.2009.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disturbance on geese in Svalbard: implications for regulating increasing tourism

Abstract: Tourism in the Arctic archipelago of Svalbard, Norway, has increased significantly in the last decade. Cruise ships make landings all around the archipelago, and there are numerous snowmobile, boat and hiking excursions. We describe disturbance effects on the three geese species that breed in Svalbard: the pink‐footed goose (Anser brachyrhynchus), the barnacle goose (Branta leucopsis) and the light‐bellied brent goose (Branta bernicla hrota). All three are regarded as highly vulnerable to disturbance. Behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…For example, inclusion of only 1 additional nest check to the sampling protocol for incubation plots at Karrak Lake would require double the personnel, adding substantial cost and logistical challenges, and increase disturbance to nests. Similar to findings of Sedinger (), increased disturbance associated with sampling for Mayfield estimation did not strongly influence nest survival in this study, although reduced disturbance has been shown to be beneficial in other situations (Bentzen et al , Madsen et al , Rizzolo et al , Gibson et al , Meixell and Flint ). The extent to which the discrepancy between apparent and Mayfield estimates is problematic can depend on the purpose of study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For example, inclusion of only 1 additional nest check to the sampling protocol for incubation plots at Karrak Lake would require double the personnel, adding substantial cost and logistical challenges, and increase disturbance to nests. Similar to findings of Sedinger (), increased disturbance associated with sampling for Mayfield estimation did not strongly influence nest survival in this study, although reduced disturbance has been shown to be beneficial in other situations (Bentzen et al , Madsen et al , Rizzolo et al , Gibson et al , Meixell and Flint ). The extent to which the discrepancy between apparent and Mayfield estimates is problematic can depend on the purpose of study.…”
Section: Discussionsupporting
confidence: 89%
“…Disturbance of nests by researchers can negatively affect nest survival (Bentzen et al , Madsen et al , Rizzolo et al , Gibson et al , Meixell and Flint ) by exposing nests to predators after displacement of parents, or by inducing abandonment. We investigated the influence of disturbance (disturb) by researchers using the model (year×age+disturb), with an index variable included in the design matrix of Program MARK that was set to 1 on the day after the nest was visited and 0 on other days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geese are highly sensitive to human disturbance, even when this does not involve persecution or habitat transformation. For example, escape flights as a response to tourist presence may significantly increase the rate of nest predation (Madsen et al 2009), and disturbance from traffic decreases feeding time in suitable pasturelands and results in habitat loss (Gill et al 1996). Southern Patagonia is one of the most remote and least populated areas in the world.…”
mentioning
confidence: 99%
“…Vegetation is characterized by Cassiope tetragona and Dryas octopetala dwarf shrubs on the slopes (Elvebakk 1997) and fen, marsh and moss tundra where freshwater accumulates (Vanderpuye et al 2002). The location of pink-footed carcasses, nesting success assessments and nest-site characteristic data were all collected after hatching because the pink-footed goose is particularly shy of humans, with nest losses after human disturbance known to be over one-third (Madsen et al 2009).…”
Section: Methodsmentioning
confidence: 99%